Medida de Mindfulness para Crianças e Adolescentes - Cunha, Marina (2018)
CAMM is a single-factor self-report measure, presenting an adequate internal consistency and test-retest reliability. It includes 10 items and all of the items are reverse scored. Total scores on the CAMM were computed by summing the responses to the 10 items, yielding a possible range of 0-40.